Fabrication and biological evaluation of titanium surfaces with multistage storage space for potential biomedical application. (17th April 2019) - Ren, Xuelei; Bian, Zeyu; Xie, Youneng; Ma, Li; Wei, Qiuping; Zuo, Jun; Wang, Xiyang; Yu, Zhiming; Zhou, Kechao; Zhang, Lei
Abstract: Bacterial infections are the main cause of failure in orthopedic implants, while drug delivery through a localized drug delivery platform is an effective solution. A novel hierarchical structure with multistage storage space was constructed in this study. Hole structures were firstly obtained by etching with a mixture of hydrogen peroxide and aqueous ammonia, and then the nanotube spaces were further constructed on this porous titanium surface by anodization. Results showed that holes of about 30 μ m in diameter were formed on the etched surface when the volume concentration of ammonia water was 7%. These holes were homogeneously distributed and the inner walls were smooth. Importantly, titania nanotube arrays on the porous surface were still grown in order without defects. In addition, the modified surface possessed excellent hydrophilicity, and cell experiments have also shown that the platform exhibited enhancing cell proliferation, vitality and osteogenic differentiation, indicating better osseointegration. Finally, the application prospects of the constructed surfaces in the localized drug delivery platform for medical implants were discussed.